Evaluation of the Caruth Police Institute at Dallas - Robert C. Davis, Radha Iyengar (RAND Corporation, 2013)
This evaluation of the Caruth Police Institute(CPI)was funded by the Communities Foundation of Texas(CFT). CPI was designed for the benefit of the Dallas Police Department to create staff development courses and to bring the expertise of academic experts and business leaders to bear on complex policing problems. The current report examines the impact of the Institute over its four-Ââ€year history. The report is intended primarily for CFT board members but is also appropriate for an audience of researchers and criminal justice practitioners interested in policing issues.